2016
DOI: 10.1001/jamainternmed.2016.4306
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects From Counterfeit Alprazolam Tablets

Abstract: the California Poison Control System-San Francisco division identified 8 patients who experienced adverse effects associated with the ingestion of counterfeit alprazolam tablets found to contain fentanyl and, in some cases, etizolam. The identification of these patients resulted in a coordinated response that included state and local public health departments, a toxicology laboratory, and media outlets, and resulted in an investigation by local law enforcement agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…This rise in NPF has created a significant public health crisis since those exposed are unaware of the adulteration, but rather assume they were using standard heroin, cocaine, or prescription strength opioid pills. Street-purchased counterfeit Xanax and Norco pills containing fentanyl were responsible for two overdose outbreaks in northern California from late 2015-2016 (Arens et al, 2016;Vo et al, 2016;Sutter et al, 2016). NPFadulteration is not limited to heroin and other illicitly produced opioid analgesics, but has also been found in cocaine.…”
Section: Study Selectionmentioning
confidence: 99%
“…This rise in NPF has created a significant public health crisis since those exposed are unaware of the adulteration, but rather assume they were using standard heroin, cocaine, or prescription strength opioid pills. Street-purchased counterfeit Xanax and Norco pills containing fentanyl were responsible for two overdose outbreaks in northern California from late 2015-2016 (Arens et al, 2016;Vo et al, 2016;Sutter et al, 2016). NPFadulteration is not limited to heroin and other illicitly produced opioid analgesics, but has also been found in cocaine.…”
Section: Study Selectionmentioning
confidence: 99%
“…A similar episode was reported in New Haven, CT, with fentanyl distributed as white powder cocaine resulting in 9 non-fatal and 3 fatal overdoses in a 6-hour period (Tomassoni et al, 2017). An outbreak of poisoning due to counterfeit alprazolam (labeled as Xanax) tablets containing fentanyl occurred in 2015 in San Francisco (Arens et al, 2016), resulting in 8 deaths and no related reports of lay naloxone use.…”
Section: Overdose Response In the Synthetic Opioid Eramentioning
confidence: 99%
“…Dependence potential, both physiological and behavioural, is documented in case reports . Few signs of harm were identified until recent years when etizolam has been involved in rapidly increasing numbers of drug‐related deaths in Scotland , and recent alerts in Australia and the USA have identified that etizolam is appearing in counterfeit benzodiazepine tablets .…”
Section: Introductionmentioning
confidence: 99%